Changes in the protein and fibre components in cassava and yam peels after solid state fermentation by aspergillus niger and rhizopus sp. (2002)
Dried, milled cassava and yam peels were inoculated separately with A. niger and Rhizopus sp in solid state. The changes in crude protein (CP), crude fibre (CF), neutral detergent fibre (NDF), acid detergent fibre (ADF) and hemiccllulose were evaluated at 0. 4. 8, and 10 days after moculation. At the end of the 10th day of fermentation with A. niger the crude protein of cassava peel meal (CPM) increased from 3.5% to 7.0% while that inoculated with Rhizopus sp increased to 5.25%. Crude protein of yam peel meal increased from 4.38% to 6.38% 10 days after inoculation with A. niger and to 7.58% with Rhizopus sp. However, the dry matter, crude fibre, NDF, ADF and hemiccllulose of both meals decreased. There was a significant difference (P < 0.05) in the degradation of CF, NDF and hemicellulose of both cassava and yam peel meals. The interaction of treatments and days had a significant effect (P < 0.05) on the level of crude protein, and degradation of CF, NDF and hemiccllulose for cassava peel meal (CPM) and yam peel meal (YPM) on inoculation with the two fungi. The pH value also decreased, with increase in the inoculation period. Simultaneous decrease in the NDF. ADF, hemiccllulose and DM with an increase in percentage crude protein content was attributed to the degradation of CF into carbon compounds (possibly simple sugar monomers) by enzymes produced by the fungi, and the utilization of these carbon compounds to build mycelial protein in the substrates. Titus the value of cassava and yam peels which are waste products of yam and cassava processing can be enhanced for livestock feeding through fungal fermentation in solid slate.